2014
DOI: 10.1007/s11748-014-0461-3
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is a perioperative risk factor and prognostic factor for lung cancer surgery

Abstract: Smokers with lung cancer tended to have advanced lung cancer, impaired pulmonary function, and high morbidity after lung cancer surgery. Although multivariate analysis did not show that smoking was associated with poor outcome, non-smokers had significantly better overall survival, even for patients with stage IA lung cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Recently, similar to our result, several reports demonstrated that preoperative smoking cessation period does not affect postoperative complications. 5,7,15,16) Groth et al 17) suggested that improvements in perioperative care including early ambulation and improvements in respiratory therapy could lead to a reduction of postoperative complications. They suggested that increases in the quality of preoperative and postoperative management and surgical procedures had decreased the impact of smoking on the development of postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, similar to our result, several reports demonstrated that preoperative smoking cessation period does not affect postoperative complications. 5,7,15,16) Groth et al 17) suggested that improvements in perioperative care including early ambulation and improvements in respiratory therapy could lead to a reduction of postoperative complications. They suggested that increases in the quality of preoperative and postoperative management and surgical procedures had decreased the impact of smoking on the development of postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Rescheduling of the surgery is necessary to ensure safe postoperative management because lung cancer surgery itself is a risk factor for developing postoperative lung injury. 4 This rescheduling policy was also implemented in our study. Therefore, the withdrawal effect of nicotine for current smokers could have been weakened, so that no difference in postoperative pain outcomes was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Thereby, the prevalence of smoking is high among patients diagnosed with lung cancer, 2 and following cancer surgery, smokers have worse outcomes than nonsmokers because of greater postoperative complications. 3 , 4 Moreover, since previous studies suggest that acute or chronic exposure to cigarette smoke affects acute and chronic painful conditions, 5 further caution needs to be exercised when providing perioperative care to patients with a smoking history and efficient strategies are needed for postoperative pain control. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Tobacco-induced immunosuppression could be another possible explanation for this effect [21, 22]. But these findings should in no way be taken to encourage patient smoking, because smoking is a risk factors for poorer survival [23, 24]. In fact, smokers often have limited pulmonary reserve, and are at a greater risk to develop respiratory failure even after a modest reduction of lung function.…”
Section: Smoking Statusmentioning
confidence: 99%